A Fintech-Backed Effective Mosque-Funds Mobilization and Collection Framework in Uganda - Hamzah, Namungo; Haji-Othman, Yusuf; Cheumar, Mohammadtahir (Yayasan Mitra Peduli Indonesia, 2023)
This paper's purpose is to explore the role financial technology (FinTech) plays in the effective finance mobilization and management in Mosques in Uganda. This paper looks into the concept of FinTech, its evolution, operation in Uganda and goes further to propose an effective framework through which it can contribution to the effective Mosque funds mobilization and management in Uganda. Financial technology, also known as FinTech, is sub-domain of information technology that is often used to underscore new technological systems that automate, speed up and effectively deliver transactions and financial information through specialized software and hardware built for specific purposes. This qualitative research aims to propose an effective FinTech-backed framework through which mosques can achieve higher funds (Zakat, Sadaqa etc.) collection margins as compared to the traditional methods.